Friars and Jews in the Middle Ages and Renaissance - Myers, Susan E.; McMichael, Steven J. (Brill, 2004)
Historians--some specializing in the Middle Ages, some in religion, and some in a particular European country--describe the major areas scholars are working in with regard to the friars' preaching to and writing about the Jews from the early days of the mendicant order about the turn of the 13th century to the 16th century. Their topics include the.
Keywords: Antisemitism -- Europe, Western -- History -- To 1500 -- Congresses.; Jews -- Europe, Western -- History -- To 1500 -- Congresses.; Friars -- Europe, Western -- History -- To 1500 -- Congresses.; Christianity and antisemitism -- Europe, Western -- History -- Congresses.; Europe, Western -- Ethnic relations -- Congresses.; Antisemitism -- Europe -- History -- To 1500 -- Congresses.; Jews -- Europe -- History -- To 1500 -- Congresses.; Friars -- Europe -- History -- To 1500 -- Congresses.; Christianity and antisemitism -- Europe -- History -- Congresses.; Europe -- Ethnic relations -- Congresses.; Antisémitisme -- Europe -- Histoire -- 500-1500 (Moyen Âge) -- Congrès.; Juifs -- Europe -- Histoire -- 500-1500 (Moyen Âge) -- Congrès.; Ordres mendiants -- Europe -- Histoire -- 500-1500 (Moyen Âge) -- Congrès.; Christianisme et antisémitisme -- Europe -- Histoire -- Congrès.; Europe -- Relations interethniques -- Congrès.; Juifs -- Europe de l'Ouest -- Histoire -- Jusqu'à 1500 -- Congrès.; Christianisme et antisémitisme -- Europe de l'Ouest -- Histoire -- Congrès.; Europe de l'Ouest -- Relations interethniques -- Congrès.; RELIGION -- Christianity -- General.; RELIGION -- Christian Life -- Social Issues.; Antisemitism; Christianity and antisemitism; Ethnic relations; Friars; Jews; Europe; Western Europe; Judentum; Mönchtum; Antisemitismus; Joden.; Religieuze orden.; Christendom.; Juden.; Saint Louis <Mo., 1997>; To 1500; Teologi -- Teologi.; proceedings (reports); Conference papers and proceedings; History; Conference papers and proceedings.; Actes de congrès.